TOTAL FENOLIK, FLAVONOID, DAN AKTIVITAS ANTIOKSIDAN DARI PRODUK TEH HIJAU DAN TEH HITAM TANAMAN BANGUN-BANGUN (Coleus amboinicus) DENGAN PERLAKUAN ETT RUMPUT PAITAN - Rahayu, Fitri; Jose, Christine; Haryani, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Coleus amboinicus is one plant with a good antioxidant content. The concentration of antioxidant from C. amboinicus could be increased by using a treatment fermented plant extract (FPE) containing paitan grass. C. amboinicus is potential to be used as raw material to produce herbal tea such as green tea and black tea because of its high antioxidant content. The objective of this study was to analyze the total phenolics, flavonoids, and antioxidant activity from tea product of C. amboinicus. Antioxidant activity was analyzed using one method, that Ferric Reducing Antioxidant Power (FRAP). The results showed that C. amboinicus treated with FPE paitan grass had the highest total phenolic, flavonoid, and antioxidant activity content than control. The green tea produced using FPE paitan grass had the highest content of total phenolic and flavonoid i.e., 25,596 Gallic Acid Equivalent (GAE) mg/g of dry weight (DW) and 5,632 Catechin Equivalent (CTE) mg/g of DW, respectively. Antioxidant activity analyzed by using FRAP method also showed that the highest antioxidant was found in green tea treated using FPE paitan grass. It can be concluded that green tea C. amboinicus treated by FPE paitan grass is a good source of phenolic, flavonoid, and antioxidant.